Towards a systematic process for the elicitation of sustainability requirements - Paech, Barbara (Requirements engineering for sustainable systems 2019, 2020)
In recent years, several approaches have been proposed in the area of sustainability requirements. They have classified sustainability into different dimensions and explored these dimensions as well as the relationships of sustainability requirements to functional requirements and quality requirements, other than sustainability. Furthermore, case studies were reported. Only a few papers describe a systematic process for deriving sustainability requirements for a specific system. In this paper, we report on work in progress on such a process. The main idea is to provide a checklist of general and IT-specific details for the sustainability dimensions and a checklist of general influences between the dimensions.